Immune-inflammatory biomarkers for the occurrence of MACE in patients with myocardial infarction with non-obstructive coronary arteries - Zhou, Hongya; Li, Xicong; Wang, Wenyuan; Zha, Yuanyi; Gao, Guanli; Li, Silin; Liu, Bei; Guo, Ruiwei (Frontiers in Cardiovascular Medicine, 2024)
Abbreviations MACE, major adverse cardiovascular events MINOCA, myocardial infarction with non-obstructive coronary arteries NHR, neutrophil-to-high-density lipoprotein cholesterol ratio MHR, monocyte-to-high-density lipoprotein cholesterol ratio LHR, lymphocyte-to-high-density lipoprotein cholesterol ratio PHR, platelet-to-high-density lipoprotein cholesterol ratio SII, systemic immune-inflammation index SIRI, systemic inflammation response index AISI, aggregate index of systemic inflammation CVD, cardiovascular disease CHD, coronary heart disease AMI, acute myocardial infarction PCI, percutaneous coronary intervention SMCs, smooth muscle cells HDL, high-density lipoprotein LDL, low-density lipoprotein ROC, receiver operating characteristic AUC, area under the curve Data availability statement: The original contributions presented in this study are included in the article/supplementary material. Further inquiries can be directed to the corresponding author. Ethics statement: Studies involving human participants were reviewed and approved by the Medical Ethics Committee of the 920 Hospital of Kunming Medical University (2015067). The patients/participants provided their written informed consent to participate in this study.Author contributions: GRW was the study guarantor, designed the project, and planned the statistical analysis. GRW, LXC, and ZHY conceived and designed the study.ZHY and LXC drafted and revised the manuscript. ZHY, WWY, ZYY, GGL and LSL collected and monitored the data collection process. All authors approved the final draft of the manuscript for publication. 48